An Analysis of Causes for Rural Youth Migrations - HemaTripathi, VB Dixit, Sajjan Singh, RekhaYadav; Inderjeet Singh (Indian Journal of Extension Education, 2018)
Large migration of youth from rural to urban areas presents a complex challenge before the academicians, researchers and policy makers and call immediate attention. Keeping in view, the present study has been taken with the research objective to explore the interests of rural youth (15-29 yrs) of Hisar district of Haryana, their thoughts forcing them for urban migration and its after effects perceived by them. The data were collected from 270 rural youth came from 18 randomly selected villages personally through an personal interview schedule. The causes of migration were categorized into push and pull factors. About eighty per cent of the respondents wished to be migrated from rural to urban areas due to one or the another reasons.About 19 per cent still showed their desire to remain in their villages and continue to be as farmer with more scientific farming. 34.44 per cent youth preferred inter-district migration followed by intra-state. About 17 per cent youth showed their desire to be migrated within the district only for more homophilous environment. 95 per cent youth revealed that better job availability in urban areas (Rank I), better educational opportunities (Rank II) and better opportunities for more income (Rank III) were the major reasons for migration revealed by 91.74 and 87.61 per cent respectively. Respondents were also asked to reveal the after effects of migration perceived by them. 62 per cent respondents felt to go back to their villages after migration and work in agriculture related with improved techniques for better earning and ranked Ist based on its mean score (2.49). The other after effects revealed by 52.96 per cent respondents that they would earn more prestige /social recognition in the eyes of villagers as most significant and ranked IInd with 2.39 of mean score. The IIIrd major after effect revealed by youth was better socio economic status of the family and better purchasing power due to migration. Covering of crops by weather insurance revealed by 83.33 per cent youth followed by readily available entrepreneurial packages/models in the villages itself with skill development programs (77.40 %), raising agricultural productivity per unit of land (70.37 %), and support of private player to spread the extension services for better awareness and adoption of improved practices (66.30 %) as most important suggestions that ranked Ist, IInd, IIIrd and IVth, respectively for reducing the migration of youth to urban areas. The findings lead to recommendations to make the agriculture as lucrative and profitable occupation as outcome of the study for harnessing the huge potential of rural youth in farming of Hisar district and of those in similar situations